Tithonia diversifolia, a different Asteraceae: its function in sustainable systems of cattle production - Murgueitio, E. (Cuban Journal of Agricultural Science, 2023)
As part of the global flora, Asteraceae family is recognized by its abundance of species, which are calculated in 23,600 (between 24,000 and 30,000) and 1,690 genera, according to the Royal Botanic Gardens at Kew in England (2022). They represent between 8 and 10 % of the world flora. They are grass, shrubs, and trees spread around the world, except in Antarctica (Global Compositae Database 2022). Around forty species have direct importance in human feeding such as vegetables (lettuce and artichokes) and oily seeds (sunflower). Through industrial processes, numerous products are extracted from hundreds of species of this family, which are used in pharmaceuticals and other economic sectors (Del Vitto and Pettenati 2009).